Chinese Herbal Formula Huayu-Qiangshen-Tongbi Decoction Compared With Leflunomide in Combination With Methotrexate in Patients With Active Rheumatoid Arthritis: An Open-Label, Randomized, Controlled, Pilot Study - Wu, Jiaqi; Chen, Xianghong; Lv, Yuan; Gao, Kaixin; Liu, Zehao; Zhao, Yue; Chen, Xiumin; He, Xiaohong; Chu, Yongliang; Wu, Xiaodong; Ou, Aihua; Wen, Zehuai; et al. (Frontiers in Medicine, 2020)
Background: Traditional Chinese Medicine is complementary and an alternative to modern medicine. The combination therapies of herbal products with disease-modifying anti-rheumatic drugs are gradually and widely adopted in the management of rheumatoid arthritis (RA) in China. Purpose: To evaluate the efficacy and safety of Huayu-Qiangshen-Tongbi (HQT) decoction, a Chinese medicine formula, combined with methotrexate (MTX) in the treatment of patients with active RA, in comparison with the combination therapy of MTX with leflunomide (LEF). Methods: This pilot study was a monocenter, open-label, randomized controlled trial with two parallel arms. Ninety patients with active RA were randomly allocated to receive either HQT at a dose of 250 ml twice daily or LEF at a dose of 20 mg once daily, and all participants received MTX at a dose of 10–15 mg once weekly. The primary efficacy endpoint was the proportion of patients who achieved a 20% improvement in the American College of Rheumatology criteria (ACR20) after a 24-week treatment. Results: 84.4% (76/90) patients completed the 24-week observation. In the intention-to-treat analysis, the percentage values of patients achieving the ACR20 response criteria were 72.1% (31/43) in MTX + HQT group and 74.4% (32/43) in MTX + LEF group (p = 0.808). No significant difference was observed in other parameters, including ACR50, ACR70, clinical disease activity index good responses, European League Against Rheumatism good response, remission rate, and low disease activity rate. The results of the per-protocol analysis showed consistency with those of the intention-to-treat analysis. The mean change from baseline at week 24 for the van der Heijde modified total sharp score had no significant difference between two groups (3.59 ± 4.75 and 1.34 ± 8.67 in the MTX + HQT group and MTX + LEF group, respectively, p = 0.613). The frequency of adverse events was similar in both groups (11 cases in the MTX + HQT and 17 cases in the MTX + LEF, p > 0.05). Conclusions: In patients with active RA, treatment with the combination of HQT and MTX was associated with improvement in signs, symptoms, and physical function. With a beneficial clinical response and acceptable tolerability, HQT or other Chinese medicine formula may be a good therapeutic option in combination with MTX for RA treatment. Trial registration: Chinese Clinical Trails Registry, ChiCTR-INR-16009031, Registered on 15th August 2016, http://www.chictr.org.cn/enindex.aspx.